DIGITAL INCLUSION AND RE-ENGINEERING EDUCATION FOR SUSTAINABLE DEVELOPMENT GOALS IN PUBLIC UNIVERSITIES IN RIVERS STATE (Scientific Journal of Educational Management, Research and law, 2026)
The study examined Digital Inclusion and Re-Engineering Education for Sustainable Development Goals in Public Universities in Rivers State. Two research questions and two hypotheses were drawn. The study adopted a descriptive survey design. The population stood at 3,762 lecturers across public universities in Rivers State, which include University of Port Harcourt, Rivers State University and Ignatius Ajuru University. The sample size which stood at 362 respondents, was determined using Taro Yamen formula. Stratified sampling technique was use in selecting the respondents, comprising of 158 male lecturers and 204 femalelecturers in public universities in Rivers State. The instrument for data collection was a self-structured questionnaire titled: “Digital Inclusion and Re-Engineering Education for Sustainable Development Goals in Public Universities Questionnaire”. The instrument was validated by two experts in the field of Measurement and Evaluation in Rivers State University. The reliability of the instrument was determined using Cronbach Alpha method. A cumulative reliability index of 0.81 was obtained. The mean and standard deviation statistics were used to answer the research questions, while the hypotheses were tested using z-test statistics at 0.05 level of significance. The findings of the study revealed that access to digital learning tools and AI-driven personalised learning enhances sustainable development goals in public universities in Rivers State. Based on the findings of the study, it was recommended, among others that, governments and private sector stakeholders should invest in broadband infrastructure, public Wi-Fi, and affordable internet services to ensure that all students, especially those in rural and underserved communities, have reliable access to digital learning resources.